Improvement in Dysphagia Outcomes Following Clinical Target Volume Reduction in the De-ESCALaTE Study. Issue 12 (December 2021) - Vreugdenhil, M.; Fong, C.; Iqbal, G.; Roques, T.; Evans, M.; Palaniappan, N.; Yang, H.; O'Toole, L.; Sanghera, P.; Nutting, C.; Foran, B.; Sen, M.; et al.
Abstract: Aims: The De-ESCALaTE study showed an overall survival advantage for the administration of synchronous cisplatin chemotherapy with radiotherapy in low-risk oropharyngeal cancer when compared with synchronous cetuximab. During the trial, a radiotherapy quality assurance protocol amendment permitted centres to swap from the original radiotherapy contouring protocol (incorporating the whole oropharynx into the high-dose clinical target volume (CTV); anatomical protocol) to a protocol that incorporated the gross tumour volume with a 10 mm margin into the CTV (volumetric protocol). The purpose of this study was to examine both toxicity and tumour control related to this protocol amendment. Materials and methods: Overall survival and recurrence at 2 years were used to compare tumour control in the two contouring cohorts. For toxicity, the cohorts were compared by both the number of severe (grades 3–5) and all grades acute and late toxicities. In addition, quality of life and swallowing were compared using EORTC-C30 and MD Anderson Dysphagia Inventory, respectively. Results: Of 327 patients included in this study, 185 were contoured according to the anatomical protocol and 142 by the volumetric protocol. The two cohorts were well balanced, with the exception of significantly more patients in the anatomical cohort undergoing prophylactic feeding tube insertion ( P < 0.001). With a minimum of 2 years of follow-up there was no significant difference in overall survival or recurrence between the two contouring protocols. Similarly, there was no significant difference in the rate of reported severe or all grades acute or late toxicity and no sustained significant difference in quality of life. However, there was a significant difference in favour of volumetric contouring in several domains of the MD Anderson Dysphagia Inventory questionnaire at 1 year, which persisted to 2 years in the dysphagia functional ( P = 0.002), dysphagia physical ( P = 0.009) and dysphagia overall function ( P = 0.008) domains. Conclusion: In the context of the unplanned post-hoc analysis of a randomised trial, measurable improvement in long-term dysphagia has been shown following a reduction in the CTV. Further reductions in the CTV should be subject to similar scrutiny within the confines of a prospective study. Highlights: An amendment during a randomised study allowed centres to adopt a contouring protocol with a reduced clinical target volume. Use of the reduced clinical target volume was not associated with a statistically significant increase in local recurrence. Use of the reduced target volume was associated with improved swallowing outcomes.